On-field signs of concussion predict deficits in cognitive functioning: Loss of consciousness, amnesia, and vacant look - Peltonen Kati; Launes Jyrki; Koskinen Sanna; Vartiainen Matti; Pajunen Sara; Pertab Jon; Laitala Tiina; Hokkanen Laura (WILEY, 2025)
The usefulness of on-field signs in predicting concussion outcome is under debate. We studied the prevalence of these signs and analyzed the predictive value for post-injury cognitive recovery in Finnish elite-level youth ice hockey players. Of the 570 consecutive athletes, 52 were concussed during seasons 2015-2017. After exclusion criterion analysis included 34 hockey players (14-20 years-old). Follow-up assessment was performed seven days post-injury and compared with pre-injury baseline. Cognitive performance was assessed using the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT (R)) battery. Hierarchical regression analyses were conducted to examine the relationship between on-field signs of concussion and the post-injury change in cognitive performance. The findings indicated that on-field loss of consciousness, amnesia, and vacant look were associated with larger decrements in cognition. Loss of consciousness accounted for 22% of the variance in verbal memory scores; amnesia accounted for 15% of the variance in verbal memory scores, and the presence of vacant look accounted for 9% of the variance in visual memory performance. The presence of loss of consciousness, amnesia, or vacant look is risk factors for longer recovery times and predict the need for extended cognitive follow-up.